Techniques for tracking the spatio-temporal movement of tourists - Xia, Jianhong (Cecilia); Basic, F.; Arrowsmith, C. (Melbourne University, 2005)
The aim of this paper is to identify suitable tracking techniques for the spatio-temporal movement behaviour of tourists in a natural environment for various applications. Several techniques at both a micro and macro scale are compared and reviewed. Each review includes a summary of advantages and disadvantages for the techniques and identifies suitable applications for each technique. Only tracking techniques will be reviewed here. The types of tracking techniques discussed includes observation and interviews, self-administered questionnaires, GPS tracking, PDA tracking and Location-Based Services (LBS), virtual questionnaires, mobile phone tracking and closed circuit television tracking. The literature review has provided guidance in choosing suitable tracking techniques for a research project that aims to model the spatio-temporal movement patterns of tourists visiting Phillip Island. This paper will provide an outline of this research project including the practical suitability of each chosen tracking technique for the Phillip Island case study.